2009
DOI: 10.1161/circulationaha.107.760819
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Brain Injury in Transposition of the Great Arteries Is Associated With Oxygenation and Time to Surgery, Not Balloon Atrial Septostomy

Abstract: Background-Preoperative brain injury is an increasingly recognized phenomenon in neonates with complex congenital heart disease. Recently, reports have been published that associate preoperative brain injury in neonates with transposition of the great arteries with the performance of balloon atrial septostomy (BAS), a procedure that improves systemic oxygenation preoperatively. It is unclear whether BAS is the cause of brain injury or is a confounder, because neonates who require BAS are typically more hypoxem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
200
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(237 citation statements)
references
References 31 publications
18
200
3
1
Order By: Relevance
“…Balloon atrial septostomy is typically performed without the use of procedural heparinization. 683 Other interventions such as the creation of atrial communications with the use of various techniques are typically done with full heparinization because most of these patients do need femoral arterial access, as well as catheterization of the left side of the heart. Specific recommendations in this regard cannot be formulated because there is a paucity of published information.…”
Section: Thromboprophylaxis For Balloon Atrial Septostomy and Transsementioning
confidence: 99%
“…Balloon atrial septostomy is typically performed without the use of procedural heparinization. 683 Other interventions such as the creation of atrial communications with the use of various techniques are typically done with full heparinization because most of these patients do need femoral arterial access, as well as catheterization of the left side of the heart. Specific recommendations in this regard cannot be formulated because there is a paucity of published information.…”
Section: Thromboprophylaxis For Balloon Atrial Septostomy and Transsementioning
confidence: 99%
“…In another study, Petit et al, in a cohort of 26 infants with TGA found periventricular leucomalacia in 38%, which was not associated with BAS but with lower preoperative oxygenation and longer time to surgery. 28 The limitations of our study include its retrospective nature and the inherent associated biases. Our sample size was small, although in line with similar studies.…”
Section: Discussionmentioning
confidence: 96%
“…However, Applegate and Lim did not find this association in 2,000 children with TGA (21). Furthermore, recent magnetic resonance imaging studies have suggested that decreased arterial oxygenation and the presence of an intact ventricular septum, and not BAS, are associated with preoperative brain injury (7,22). Nevertheless, the risk of thrombosis remains a possible adverse risk factor associated with BAS.…”
Section: Discussionmentioning
confidence: 98%
“…Magnetic resonance imaging studies demonstrate that 25-40% of neonates with complex congenital heart disease already have evidence of brain injury before surgery (6)(7)(8)(9). Severe preoperative hypoxia and acidosis have already been identified as predisposing factors to preoperative brain injury and motor delay in school-aged children with TGA (3,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation